Increased ict competence teachers classroom in teaching process through supervision in teachers Sd negeri no.002 tualang kecamatan tualang - Ellia Ningsih (Jurnal Ilmiah Pendidikan Scholastic, 2018)
There is an increase in ICT Competence Teachers Classroom In Teaching and Learning Process Through Supervision In Primary School Teachers No.002 Tualang District Tualang Siak District. This research is motivated by (a) the low level of competence of non-ICT class teachers, (b) the number of classroom teachers is only competent in certain subject areas not ICT, (c) not all class teachers, especially those with honorary status, Upgrading or training of ICT, and (d) the rarity of ICT-based TCTK ICT activities specifically to discuss the ICT, so that the lesson plans are rarely even never used ICT. With the aim to know (a) the influence of ICT Teacher Competence Improvement in Teaching and Learning Process by Supervisi in Teacher of State Elementary Class No.002 No.002 Tualang Kecamatan Tualang Lesson Year 2015/2016, and (b) activity of class teacher in using media of technology (2) the implementation of corrective action, (3) observation, and (4) reflection. The results showed that (a) there was an increase in ICT competence of Class Teachers Through Supervision In Primary School Class Teachers No.002 Tualang Tualang District Siak District. Assessment through the Rubric of Assessment of the Implementation Plan The lessons in cycle 1, which reached 119 points, were in good category, and the results of the second cycle of achieving 151 grades were in very good categories, and (b) teacher activity in the second cycle of learning Good than at the time of the first cycle. Assessment through the Student Activity Rating Rubric in the teaching and learning process during the first cycle which reaches a grade of 30 or is classified as good, and in the second crosses reaches a value of 36, which means very good. Based on the results of this study the authors recommend to the classroom teachers to optimize their role as planners, organizers, and learning actors, to head UPTD Education District Tualang to facilitate classroom teachers to improve ICT competence so that the impact on improving the quality of education in schools, to the Education Office Siak District , To more frequently facilitate ICT Training activities by involving them in various training so as to improve the quality of education in SD Negeri No.002 Tualang in particular and Siak Regency in general.